2021
DOI: 10.1088/1757-899x/1166/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Review on solid-liquid separation using various conditioning methods

Abstract: The increase in industrialization and population in the recent days the sludge production is also increased which has become difficult to handle it. Sludge used to be incinerated, compost and landfilling before disposal, but as it is not economic and environmentally friendly most of researchers are concentrating on the sludge dewatering process which are sustainable technologies so that sludge can be converted to semi solid which will be easy to handle and transport. Some sludge is used to produce to biogas, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…66 Only through high temperature, flocculation, chemical oxidation, biodegradation, and other conditioning methods to modify and adjust the sludge, or by destroying the structure of the sludge cell and EPS, can the bound water be transformed into free water, to attain the purpose of deep dehydration. 67 In recent years, many useful conditioning methods have been employed to alter the physicochemical properties of sludge, for achieving an effective reduction of volume and contributing to the subsequent utilization of resources. 68 The commonly used methods of sludge modification are the physical method, chemical method, biological method, and hybrid conditioning method.…”
Section: The Methods Of Sludge Conditioning For Dehydrationmentioning
confidence: 99%
“…66 Only through high temperature, flocculation, chemical oxidation, biodegradation, and other conditioning methods to modify and adjust the sludge, or by destroying the structure of the sludge cell and EPS, can the bound water be transformed into free water, to attain the purpose of deep dehydration. 67 In recent years, many useful conditioning methods have been employed to alter the physicochemical properties of sludge, for achieving an effective reduction of volume and contributing to the subsequent utilization of resources. 68 The commonly used methods of sludge modification are the physical method, chemical method, biological method, and hybrid conditioning method.…”
Section: The Methods Of Sludge Conditioning For Dehydrationmentioning
confidence: 99%
“…The process of sediment framework construction has attracted attention due to its ability to directly modify the physical properties (compressibility and permeability) of the sediment cake through the addition of inert rigid materials. With in-depth research, scientists have found that these materials show greater potential in terms of preparation and transportation costs, environmental friendliness, and waste recycling [16]. Thanks to this, frame construction has gained significant development in recent years.…”
Section: Introductionmentioning
confidence: 99%